The quest for the lost nation : writing history in Germany and Japan in the American century - Conrad, Sebastian (Berkeley : University of California Press, 2010)
Highly praised when published in Germany, The Quest for the Lost Nation is a brilliant chronicle of Germany's and Japan's struggles to reclaim a defeated national past. Sebastian Conrad compares the ways German and Japanese scholars revised national history after World War II in the shadows of fascism, surrender, and American occupation. Defeat in 1945 marked the death of the national past in both countries, yet, as Conrad proves, historians did not abandon national perspectives during reconstruction. Quite the opposite--the nation remained hidden at the center of texts as scholars tried to mak.
Cover; Contents; Introduction; 1. Mapping Postwar Historiography in Germany and Japan; 2. The Origin of the Nation: Bismarck, Meiji Ishin, and the Subject of History; 3. The Nation as Victim: Writing the History of National Socialism and Japanese Fascism; 4. The Invention of Contemporary History; 5. The Temporalization of Space: Germany and Japan between East and West; 6. History and Memory: Germany and Japan, 1945-2000; Notes; Bibliography; Acknowledgments; Index; A; B; C; D; E; F; G; H; I; J; K; L; M; N; O; P; R; S; T; U; V; W; Y; Z.
Includes bibliographical references (p. 303-376) and index.
Translated from the German.
Description based on print version record and CIP data provided by publisher; resource not viewed.
JSTOR
Keywords: Germany -- Historiography; Japan -- Historiography; Historiography -- Germany -- History -- 20th century; Historiography -- Japan -- History -- 20th century; World War, 1939-1945 -- Influence; World War, 1939-1945 -- Social aspects -- Germany; World War, 1939-1945 -- Social aspects -- Japan; Cold War -- Social aspects -- Germany; Cold War -- Social aspects -- Japan; Guerre mondiale, 1939-1945 -- Influence; Guerre mondiale, 1939-1945 -- Aspect social -- Allemagne; Guerre mondiale, 1939-1945 -- Aspect social -- Japon; Guerre froide -- Aspect social -- Allemagne; Guerre froide -- Aspect social -- Japon; Historiographie -- Allemagne -- Histoire -- 20e siècle.; Historiographie -- Japon -- Histoire -- 20e siècle.; HISTORY; HISTORY -- Asia -- General; Historiography; Influence (Literary, artistic, etc.); Social aspects; Germany; Japan; 1900 - 1999; History